KEJAHATAN PERANG OLEH JEPANG (STUDI KASUS TERHADAP JUGUN-IANFU SEBAGAI HEGEMONI KEBUDAYAAN DI INDONESIA PERIODE 1942-1945) - Dewi Savitri (Jurnal Kriminologi Indonesia, 2010)
After Japanese taking over Indonesia from the Dutch, they have built military bases across the country. Every one of it is completed with adjunct comfort station, a place for serving Japanese army's biological needs. Comfort station is filled with Indonesian women called jugun-ianfu. Jugun-ianfu is a form of concentrated systematic rape. Jugun-ianfu is a value system that Japanese brought to Indonesia. And yet, it is a form of crime that Japanese conduct to Indonesian women. It is an ideal value system for Japanese, not Indonesian women. They have tried to impose their culture values over Indonesian women. Culture hegemony is a term that never discussed comprehensively in jugun-ianfu discourse. It was only explain about victim's condition, Indonesian's social condition and jugun-ianfu's related law process. This research's purpose is to discuss how jugun-ianfu could be seen as Japanese culture hegemony over Indonesia. This research utilizes qualitative method in order to yields descriptive data as a result. Thus could represent Japan's social condition before and after their presence in Indonesia, Indonesia's social condition and form of hegemony which Japanese have creates. The data has divided to primary and secondary. Primary data obtained from deep interview with Mr. Mardiyono (late Mrs. Mardiyem's son), Mr. Budi Hartono (late Mrs. Mardiyem's lawyer), and Dwi Mulyatari (Indonesian History tutor staff at Cultural Science Faculty, University of Indonesia). Then the secondary data obtained from literatures and newspaper clipping related to jugun-ianfu.